Development of four‐terminal DC circuit breaker based on commutating path multiplexing - Zhizheng Gan; Bojin Tang; Zhanqing Yu; Jinshi Wang; Lu Qu; Na Jia; Xin Yan; Mingzhu Guo; Rong Zeng; Yulong Huang (IET Generation, Transmission & Distribution, 2023)
Abstract Multi‐terminal flexible DC power grid plays an important role in large‐scale new energy integration, which usually requires the installation of multi‐terminal DC circuit breaker (MTCB) at the intersection of multiple DC lines. At present, the research on multi‐terminal DC circuit breaker is mostly limited to theoretical simulation calculation, and there are few experimental studies and engineering applications. In this paper, a four‐terminal DC circuit breaker based on commutating path multiplexing is proposed, which combines with the compact natural commutation scheme of hybrid gap, greatly reducing the cost and volume of the circuit breaker. The commutation characteristics of the four‐terminal hybrid DC circuit breaker equivalent prototype at 10‐kV voltage level were tested. On this basis, the equivalent prototype of the circuit breaker test results shows that under 10‐kV voltage level, the four‐terminal circuit breaker topology can achieve breaking of 11 kA in 2.8 ms by the natural commutation method.